Vegetation type and plant diversity affected soil carbon accumulation in a postmining area in Shanxi Province, China. (31st October 2019) - Yan, Meifang; Cui, Feifei; Liu, Yang; Zhang, Zeyu; Zhang, Jianbiao; Ren, Hongrui; Li, Zhiping
Abstract: Coal mining causes severe land degradation, which poses a great damage to carbon (C) sequestration function of the original ecosystem. Vegetation restoration in postmining areas plays an important role in rebuilding soil C pool and improving soil quality. In this study, soil C sequestration and soil properties of different vegetation types were investigated along restoration chronosequences in a postmining area in the eastern Loess Plateau. The results showed that soil properties improved substantially through artificial restoration by planting Rhus typhina (exotic species) and Platycladus orientalis (indigenous species) and through natural restoration. Soil C stock (0–20 cm depth) increased significantly with restoration duration in all of the vegetation types and was positively correlated to plant diversity except in R. typhina . After 12–20 years from restoration, accumulation rates of soil C varied significantly with vegetation type, with the maximum in P. orientalis (0.60 Mg ha −1 yr −1 ) and the minimum in naturally restored grassland (0.21 Mg ha −1 year −1 ). The optimum performance of P. orientalis plantation could be attributed mainly to high plant diversity and associated high fine root biomass (1.72 Mg ha −1 ). A sharp decrease of plant diversity (39.0%) in R. typhina 12 years after restoration implied that soil C accumulation might not be sustainable in the long term. Our results suggest that P. orientalis as an indigenous species adaptable to harsh environment may facilitate the succession of a diverse ecosystem and promote soil C accumulation in degraded lands of postmining areas.